2013
DOI: 10.1002/ajh.23354
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin levels predict nonresponsiveness to oral iron therapy in patients with iron deficiency anemia

Abstract: Levels of hepcidin, a major regulator of iron homeostasis, may identify patients with iron deficiency anemia (IDA) who will not respond to oral iron therapy. In this study, IDA patients underwent a 14-day trial (run-in) course of ferrous sulfate therapy. Nonresponders (Hgb increase <1 g/dL with 67% compliance rate) were randomized to IV ferric carboxymaltose (FCM; two injections of 750 mg) or further oral iron for 14 days. Screening hepcidin levels were 38.4 versus 11.3 ng/mL, P 5 0.0002 in nonresponders versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
1
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(135 citation statements)
references
References 21 publications
5
111
1
11
Order By: Relevance
“…Thus, CHF represents a paradigmatic condition where recent pathophysiological insights on hepcidin appear to influence the choice on the most appropriate route of iron administration. The same concept was previously suggested by two retrospective studies in cancer patients [77], and in unselected IDA patients [78], where baseline hepcidin levels predicted subsequent responsiveness to oral iron. After initial technical difficulties, hepcidin assays are continuously improving, and a number of them showing good accuracy and reproducibility have been internationally validated [25].…”
Section: Oral Iron Therapy In the Hepcidin Eramentioning
confidence: 51%
“…Thus, CHF represents a paradigmatic condition where recent pathophysiological insights on hepcidin appear to influence the choice on the most appropriate route of iron administration. The same concept was previously suggested by two retrospective studies in cancer patients [77], and in unselected IDA patients [78], where baseline hepcidin levels predicted subsequent responsiveness to oral iron. After initial technical difficulties, hepcidin assays are continuously improving, and a number of them showing good accuracy and reproducibility have been internationally validated [25].…”
Section: Oral Iron Therapy In the Hepcidin Eramentioning
confidence: 51%
“…14,15 A recent study demonstrated that hepcidin levels predict nonresponsiveness to oral iron in non-HF patients with iron deficiencye anemia. 16 Unfortunately, circulating levels of hepcidin were not available in the present retrospective analysis. Gut edema is also suspected to play a role in impairing the absorption of oral iron that predisposes HF patients to iron deficiency.…”
Section: Discussionmentioning
confidence: 98%
“…Because hepcidin directly controls iron absorption, 4,5 serum hormone levels have the potential to predict poor responsiveness to oral iron, preventing possible detrimental effects of oral iron on the gut microbiome and metabolome 68 and eliminating delays before switching to IV iron. The usefulness of measuring basal hepcidin to personalize the optimal route of iron administration has been recently showed in patients with IDA, 62 chronic rheumatic anemia, 32 and chemotherapy-associated anemia. 63 However, large prospective trials are needed to confirm this attractive hypothesis.…”
Section: Diagnosis and Management Of Idamentioning
confidence: 99%